Laser as a tool to measure the diameter of goat hair (Capra aegagrus hircus) - Rani Rahmawati; Widi Komariah; Helmina Pebriyanti; Dedeh Sukmawati; Siti Rusmiati; Retno Nopita; Eko Sujarwanto (Universitas Riau, 2024)
Measuring the diameter of objects that have dimensions less than 1/100 mm has a high degree of difficulty. The use of a micrometer is still not able to make these measurements. One way that can be used is to use the concept of diffraction. The purpose of this study was to measure the diameter of goat hair using the concept of diffraction. The tools used are a laser with a red wavelength, a screen, support, and specimens of goat hair. Measurements were taken three times with results of 13.9 × 10-5, 11 × 10-5, and 8 × 10-5 m. The diameter values obtained from this experiment are still within the diameter range of mammalian hair, which is on the order of 10-5 m. Based on this experimental activity, it can also be seen that hair can be used to demonstrate the phenomenon of diffraction due to the characteristics of hair being filamentous and has a diameter close to the wavelength of light from a laser, so that it can produce a diffraction pattern when light is passed through the laser.